Early Metastasis in Different Types of Breast Carcinoma - A Personal Experience - Rahman, ATM Mostafizur (Anwer Khan Modern Medical College Journal, 2021)
Background: Carcinoma breast is one of the leading causes of death in woman today and is the most common cancer among women. More than 2.3 million of women are diagnosed breast cancer each year world-wide. Carcinoma breast may present from an extent of non-palpable lump to a fixed mass with distal metastasis. As presentation is highly variable, management strategy varies even in same stage of disease. Objective: To identify early metastasis of different types of breast carcinoma and its management. Materials and methods: This is a prospective type of observational study in 100 cases done in the different surgical units of Dhaka Medical College Hospital (DMCH), Bangabandhu Sheikh Mujib Medical University (BSMMU) and Bashundhara Ad-din Medical College Hospital (BAMCH).Patients were selected clinically and by some standard investigation (FNAC and core biopsy) from January 2006 to December 2018. Result: Patients at different age groups had suffered from different types of breast carcinoma. Early diagnosis by triple assessments and proper surgical and post-surgical managements reduced both loco- regional and distant metastasis and also reduced both morbidity as well as mortality. Results of treatment and histopathological reports were recorded. It was found that FNAC is cheap and minimally invasive diagnostic procedure with high sensitivity (100%) and specificity (95%).Core needle biopsy is more accurate tissue diagnostic in breast cancer. Down staging has profound symptomatic and cosmetic benefit. In renders inoperable tumors become operable and reduce morbidities. Conclusion: Early diagnosis and treatment is the mainstay to achieve satisfactory outcome. Screening program especially Self-Breast Examination (SBE) is very much helpful in early diagnosis of disease in our social setting. Screening mammography has had the most substantial impact on the early diagnosis of, and subsequent decrease in mortality from breast carcinoma. Women of 20-40 years of age should have a breast examination every 2-3 yearly. Women of more than 40 years of age should have a breast examination every yearly. AKMMC J 2022; 13(1) : 14-21